KISAH (STORYTELLING) PADA PEMBELAJARAN ANAK USIA DINI DALAM KAJIAN NEUROSAINS PENDIDIKAN ISLAM - Suyadi Suyadi (Islam Futura, 2018)
Religious, inspirational, and motivational storytelling can develop hard a work ethic, and also cultivate spirituality that implicates the nation's progress. On the contrary, storytelling that "lulled" people will make the nation's generation become lazy, thus do not have work hard ethic. Children's stories in Indonesia are still contaminated with Isra'iliyat stories and contain trickery, even mystique, and sexual contents. Therefore it has implications for the nation's condition which is corrupt, adolescent free-sex, and rampant practice of political shamanism. This research examines the storytelling in Early Childhood Education in the study of the neuroscience of Islamic education. The research setting was conducted at Early Childhood Education institutions in Yogyakarta. This research was using a descriptive qualitative approach. Research data were children's storybooks and storytelling methods in early childhood learning practices. Elements of children's stories were analyzed in descriptive, interpretative, and comparative ways based on neuroscience learning theories, thus can be known which stories fit the brain work characteristics. The results showed that children's stories can be divided into three, which are robotic stories, the stories that could be damaging children's brain potential; academic stories, stories that could be emasculating children's brain; and scientific stories or neurostory telling, the stories that have the potential to optimize the children's brain.